A High-Throughput RNA Displacement Assay for Screening SARS-CoV-2 nsp10-nsp16 Complex toward Developing Therapeutics for COVID-19. (June 2021) - Perveen, Sumera; Khalili Yazdi, Aliakbar; Devkota, Kanchan; Li, Fengling; Ghiabi, Pegah; Hajian, Taraneh; Loppnau, Peter; Bolotokova, Albina; Vedadi, Masoud
SARS-CoV-2, the coronavirus that causes COVID-19, evades the human immune system by capping its RNA. This process protects the viral RNA and is essential for its replication. Multiple viral proteins are involved in this RNA capping process, including the nonstructural protein 16 (nsp16), which is an S -adenosyl-l -methionine (SAM)-dependent 2′- O -methyltransferase. Nsp16 is significantly active when in complex with another nonstructural protein, nsp10, which plays a key role in its stability and activity. Here we report the development of a fluorescence polarization (FP)-based RNA displacement assay for nsp10-nsp16 complex in a 384-well format with a Z′ factor of 0.6, suitable for high-throughput screening. In this process, we purified the nsp10-nsp16 complex to higher than 95% purity and confirmed its binding to the methyl donor SAM, the product of the reaction, S -adenosyl-l -homocysteine (SAH), and a common methyltransferase inhibitor, sinefungin, using isothermal titration calorimetry (ITC). The assay was further validated by screening a library of 1124 drug-like compounds. This assay provides a cost-effective high-throughput method for screening the nsp10-nsp16 complex for RNA competitive inhibitors toward developing COVID-19 therapeutics.